Ripples in the Stream: Social Transition and Self-Organization - Newman, Rob (UnderCurrents: Journal of Critical Environmental Studies, 2001)
As human society struggles to adjust to a growing variety of ongoing changes, understanding how human society adapts to challenges has become a vital avenue of research.